U.S. racial and ethnic participation in global clinical trials by therapeutic areas - Lolic, Milena; Araojo, Richardae; Okeke, Melvyn; Temple, Robert (Journal of clinical pharmacy and therapeutics, 2021)
What is known and objective The discussion about health equity in the United States frequently involves concerns over racial and ethnic minority under‐representation in clinical trials and particularly in trials conducted in support of product approvals. The FDA has long worked to encourage diverse participation in clinical trials and through its Drug Trials Snapshots (DTS) program, the U.S. Food and Drug Administration (FDA) has moved to make trial demographic data more accessible and transparent. We conducted a demographic study of U.S. participants in clinical trials for FDA‐approved new drugs (new molecular entities [NMEs], and original Biologics License Applications [BLAs]) from 2015 to 2019, as reported in DTS database with a purpose of understanding the extent to which U.S.‐based trials used to support product approvals represent the racial and ethnic diversity of the U.S. population by therapeutic area. Methods Participant‐level trial data were collected by accessing the FDA electronic common technical document (eCTD), for the applications used to publish each Snapshot. The therapeutic area (TA) for each drug was determined by review division assignment. The demographic data were analysed and compared to U.S. census data. Results and discussion We examined 102,596 U.S. participants in trials of new drugs that were approved and presented in Drug Trials Snapshots between 2015 and 2019. White participation ranged from 51% in psychiatric trials to 90% in cardiovascular (CV) trials; Black or African American participation ranged from 5% in medical imaging to 45% in psychiatric trials; Asian participation ranged from 0.75% in CV to 4% in dermatologic trials; and Hispanic or Latino participation ranged from 1% in medical imaging to 22% in infectious diseases and gastroenterology trials. What is new and conclusion Our data showed variable representation of racial and ethnic minorities across therapeutic areas at the U.S. sites. Blacks or African Americans were represented at or above U.S. census estimates across most therapeutic areas, while Asians and American Indian or Alaska Natives were consistently underrepresented. Hispanic or Latino participation across most therapeutic areas was below U.S. census estimates, however, more variable, and a sizable proportion of data was missing. The next step is a comparison of trial participation based on disease prevalence and epidemiology, which is a more accurate assessment of trial diversity. We conducted a demographic study of U.S. participants in clinical trials for FDA‐approved new drugs from 2015 to 2019. U.S. participation within each therapeutic area ranged from 18% in Cardiovascular Diseases to 82% in Ophthalmology and was notable for variable representation of minorities across therapeutic areas.